GAMBARAN FUNGSI KOGNITIF PADA PENDERITA HIPERTENSI USIA 45-59 TAHUN DI PUSKESMAS TLOGOSARI WETAN KOTA SEMARANG - Deni Lestari; Ari Udiyono; Lintang Dian Saaraswati; M. Sakundarno Adi (Jurnal Kesehatan Masyarakat (Undip), 2018)
Cognitive impairment is a disorder which a person is experiencing a memory loss more severe than people his age. The causes are multifactorial, one of which is hypertension. The purpose of this study was to describe the cognitive function in patients with hypertension aged 45-59 years in the primary health care center Tlogosari Wetan, Semarang City. This research used descriptive research with cross-sectional study design. There were 100 respondents with hypertension who meet the admission criteria as research subjects. The sample was selected by simple random sampling. The result showed that the proportion respondents with cognitive impairment was 94.0%. Based on the variables researched, the percentage of cognitive impairment that occur in the age group 55-59 years (100.0%), female gender (95.1%), not completed primary school education and completed primary school eduation (100.0%), systolic blood pressure 187-202 mmHg and 172-186 mmHg (100.0%), diastolic blood pressure 107-112 mmHg and 102-106 mmHg (100.0%), long suffering hypertension ≥ 5 years (97.3%), not comsumption of antihypertensive drugs (100.0%). The proportion of higher cognitive impairment in the age group 55-59 years, female gender, systolic blood pressure 187-202 mmHg and 172-186 mmHg, diastolic blood pressure 107-112 mmHg and 102-106 mmHg, long suffering from hypertension ≥ 5 years, and not comsumption of antihypertensive drugs. Patients with hiypertension are recommended to control blood pressure in order to remain stable.